The Effect of Storage Temperatures on Quality of Minimally Processed Cantaloupe Melon (Cucumis melo L.) with Cassava Starch Based Edible Coating Application - Asri Widyasanti; Sarifah Nurjanah; Rizika Wulandari; Efri Mardawati (Journal of Industrial and Information Technology in Agriculture, 2017)
Minimally processed Cantaloupe melon has a short life because it contains high water content which is speeding up the process of spoilage. The objectives of the research were to determine the stearic acid addition on edible coating from cassava starch with low temperature storage to maintain the quality and to extend the minimally processed melon shelf life. This research used a factorial randomized complete design. Edible coating solutions were composed of 3 % cassava starch (w/v), 1 % carbo methyl cellulose (w/v) and 5 % glycerol (v/v). The treatments consisted of two factors, the first factor was the stearic acid addition on edible coating of 4 levels (0%, 0.5%, 1%, and 1.5%) and the second factor was low temperature storage with 2 levels (5°C and 10°C) with three replications. Observed parameters were respiration rate, moisture content, total titratable acidity, total soluble solids, color and weight loss. Results of this research showed that the best treatment of processed Cantaloupe was the temperature storage of 5°C and the 1.5% stearic acid addition for 5 days storage with respiration rate 33.59 mgCO2/kg hour; moisture content 8.48% (d.b.) ; total titratable acidity  38%; total soluble solid content 6.17 obrix; Hue angle 88.79o (yellow); and weight loss 5.85%.